Analyzing Switching Intention to Fintech-Based Crowdlending Services: A Push-Pull-Mooring Model - Dimas Bagus Wiranatakusuma; Virgiawan Andhika; Anggi Aprizal; Ghalieb Mutig Idroes (Jurnal Ilmu Manajemen Profitability, 2026)
The rapid growth of financial technology has transformed financial services, particularly through fintech-based crowdlending platforms that offer alternatives to conventional banking. Despite their potential advantages, switching from traditional banks to crowdlending remains limited, even among digitally literate university students. Prior research has focused primarily on adoption intention, with limited attention to the combined roles of dissatisfaction, attractiveness, and behavioral constraints in shaping switching decisions. This study examined the determinants of switching intention to fintech-based crowdlending using the Push–Pull–Mooring framework. A quantitative design was employed, and primary data were collected through structured questionnaires from 267 undergraduate economics students at Universitas Muhammadiyah Yogyakarta, Indonesia. Data were analyzed using Partial Least Squares–Structural Equation Modeling to test measurement validity and structural relationships. The findings revealed that pull factors relative advantage, perceived security, and ease of use—positively and significantly influenced switching intention (β = 0.179; p < 0.01). Push factors, including dissatisfaction with pricing, service quality, and product features, showed no significant effect (β = −0.002; p > 0.05). Mooring factors, such as inertia, affective commitment, and perceived switching costs, exerted a significant negative influence (β = −0.166; p < 0.05). These results indicate that switching intention is driven more by perceived benefits of alternatives than by dissatisfaction, while psychological and transactional barriers remain critical constraints.